Application of Medical Savings Accounts in Health Care Financing - a Household’s Perspective - Borda , Marta (Studia Oeconomica Posnaniensia, 2016)
The purpose of this paper is to analyze selected aspects of the application of Medical Savings Accounts in the private healthcare financing from a household’s perspective. A Medical Savings Account (MSA) represents an innovative and relatively seldom-used mechanism of healthcare financing, which relies on the accumulation of personal savings to cover the costs of healthcare services at the time of consumption. The paper focuses on the consideration of MSAs in household financial decisions through the presentation of issues related to MSA product selection, based on two theoretical models. The considerations conducted with the use of the first model indicate potential application of MSAs in the accumulation of long-term savings for financing healthcare expenses after retirement. The analysis conducted on the basis of the second model leads to the conclusion that more healthy people choose cheaper insurance combined with MSA, while less healthy consumers stay with more expensive traditional insurance.